Psychological and pedagogical support of youths when developing their competence in the social activity manifestation - Irina V. Arendachuk; Natalia V. Usova (Saratov State University, 2022)
The relevance of the research is determined by the public demand for the development of scientifically based programs of work with modern young people that allow developing youths' social activity. The objective of the study is to design the technology of psychological and pedagogical support of youths in their social activity manifestation that is based on the theoretical model of its structural and functional organization. The research hypothesizes that psychological and pedagogical support of young people in the manifestation of their social activity will be effective if it is designed on the basis of a scientifically grounded technology based on the concept of a systemic (structural and functional) approach. The research methods include theoretical analysis on the problem of social activity and social competence of the youth; structural and functional analysis; content analysis; theoretical modeling and design. The article shows the correlation between the social competence and social activity of the individual. The authors have developed and theoretically substantiated a model of the personal competence in the manifestation of their social activity, that reflects the structural and functional organization of a person's social competence and the system of its correlations with social activity. On the basis of the developed model, the authors have designed the technology of psychological and pedagogical support of youths that is based on the principles of the system-activity approach. The technology includes the description of the forms and methods of work with young people that correspond to the four stages of its implementation - content-evaluating, organizational-technological, implementation, and resulting stages. In solving the youth policy tasks, the presented technology allows for systematically organized work with modern youths aimed at increasing their competence in the social activity manifestation in various forms of socially-oriented activities.